Association between dynapenic obesity phenotypes and physical performance in middle-age and older women living in community - Arteaga-Pazmiño, Cecilia; Fonseca-Pérez, Diana; Balladares Mazzini, Manuel; Galvez-Celi, Javier; Emén Sánchez, Janet; Álvarez-Córdova, Ludwig (Frontiers in Nutrition, 2024)
Background: Dynapenic obesity (DO) is the coexistence of excess adipose tissue/body weight and low muscle strength. This condition is associated with an increased risk of suffering from various chronic diseases and physical deterioration in older people. Aim: To analyze the association between DO phenotypes and physical performance in middle-aged women living in the community. Methods: This cross-sectional study was conducted on middle-aged and older women (≥50 years) residing in Guayaquil, Ecuador. Dynapenia was diagnosticated by a handgrip strength (HGS) < 16 kg; obesity was determined based on body mass index (BMI) ≥ 30 kg/m 2 . Participants were categorized into four groups based on their dynapenia and obesity status: non-dynapenic/non-obesity (ND/NO), obesity/non-dynapenic (O/ND), dynapenic/non-obesity (D/NO) and dynapenic/obesity (D/O). Physical performance was assessed by the Short Physical Performance Battery (SPPB). Results: A total of 171 women were assessed. The median (IQR) age of the sample was 72.0 (17.0) years. Obesity and dynapenia were 35% (n = 60) and 57.8% (n = 99) of the participants, respectively. The prevalence of ND/NO was 25.1% (n = 43), O/ND 17% (n=29), D/NO 39.8% (n=68) and DO 18.1% (n=31). The mean SPPB total score was 6.5 ±3.2. Participants of D/NO and DO groups presented significantly lower mean SPPB scores (p < 0.001) compared to those of NO/ND and O/ND groups. Conclusion: Women with DO and D/NO exhibited significantly lower SPPB scores, indicating poorer physical performance. These findings emphasize the importance of incorporating a comprehensive assessment of muscle strength and obesity in middle-aged and older women.